MOTIVASI PETANI DALAM PENGGUNAAN JASA KOPERASI SERBA USAHA PERTIWI HIJAU - Mutiara Putri Gita Cahyani; Kadhung Prayoga; Agus Subhan Prasetyo (Universitas Galuh, 2022)
Weak capital and market information encourage farmers to access agricultural institutions, one of which is cooperatives. Most farmers prefer using the services of middlemen to cooperatives. This condition is influenced by differences in farmers' use of services, one of which is motivation. This study aims to (1) analyze the motivations of farmers to use and not use cooperative services; and (2) analyze the impact of needs, production facility availability, ability to develop, opportunities for advancement, credit availability, credit procedures, market guarantees, environmental conditions, and policy agencies on farmer motivation in using cooperative services. This research was conducted from February to March 2022 in Dlepih Village, Tirtomoyo District, Wonogiri Regency. The research method used a survey method. The sampling method used a complete enumaration method with 36 farmers as respondents. The data used was primary and secondary data. Data collection was done by interviews and observation. The data was analyzed using descriptive analysis and multiple linear regression analysis. The result showed that farmers' motivation for using and not using cooperative services fell into the high category. The t-test demonstrates that need, ability to improve, opportunity to progress, market guarantees, and agency rules have a significant positive effect, while price affordability has a significant negative effect on farmers' motivation. As a result, it's critical to recognize the importance of understanding agricultural institutions, as well as changes in service, organizational, and financial readiness.